2014
DOI: 10.1111/hsc.12095
|View full text |Cite
|
Sign up to set email alerts
|

Literature review: use of respite by carers of people with dementia

Abstract: Respite care is a cornerstone service for the home management of people with dementia. It is used by carers to mitigate the stress related to the demands of caring by allowing time for them to rest and do things for themselves, thus maintaining the caring relationship at home and perhaps forestalling long-term placement in a residential aged care facility. Despite numerous anecdotal reports in support of respite care, its uptake by carers of people with dementia remains relatively low. The aim of this paper wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
103
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 77 publications
(211 reference statements)
3
103
0
6
Order By: Relevance
“…The partnership between caregiver, care recipient, and respite provider should be the central component of respite service, although caregiver and care recipient may have different outlooks and benefit in different ways from respite care. The present study found that the caregivers would accept volunteer respite care as long as the dependent person felt or appeared comfortable and agreed to letting another person care for him or her, which has also been reported by other authors (Greenwood et al, 2012; Neville, Beattie, Fielding, & MacAndrew, 2015; Stirling et al, 2014) and highlights the importance of the relationship between all three stakeholders.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The partnership between caregiver, care recipient, and respite provider should be the central component of respite service, although caregiver and care recipient may have different outlooks and benefit in different ways from respite care. The present study found that the caregivers would accept volunteer respite care as long as the dependent person felt or appeared comfortable and agreed to letting another person care for him or her, which has also been reported by other authors (Greenwood et al, 2012; Neville, Beattie, Fielding, & MacAndrew, 2015; Stirling et al, 2014) and highlights the importance of the relationship between all three stakeholders.…”
Section: Discussionsupporting
confidence: 88%
“…The present study further examines these obstacles to a successful partnership, also relating the desirable traits of the volunteer, where the caregivers consider that the person providing the care, whether paid or voluntary, provide emotional support and have knowledge on caring for elders; at the same time, it is of the highest importance that the person have prior experience in this work (Greenwood et al, 2012; Neville et al, 2015; Stirling et al, 2014). Another desirable characteristic of the volunteer, reported by the caregivers, is that they should belong to a volunteer service institution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations